Valuing Convertible Bonds Based on LSRQM Method - Jian Liu; Lizhao Yan; Chaoqun Ma (Discrete Dynamics in Nature and Society)
Convertible bonds are one of the essential financial products for corporate finance, while the pricing theory is the key problem to the theoretical research of convertible bonds. This paper demonstrates how to price convertible bonds with call and put provisions using Least-Squares Randomized Quasi-Monte Carlo (LSRQM) method. We consider the financial market with stochastic interest rates and credit risk and present a detailed description on calculating steps of convertible bonds value. The empirical results show that the model fits well the market prices of convertible bonds in China’s market and the LSRQM method is effective.